Efficiency of Biosynthesized Silver and Zinc Nanoparticles Against Multi-Drug Resistant Pathogens - Punjabi, Kapil; Mehta, Sourabh; Chavan, Rujuta; Chitalia, Vidushi; Deogharkar, Dhanashree; Deshpande, Sunita (Frontiers in Microbiology, 2018)
Biosynthesis of metallic nanoparticles has acquired particular attention due to its economic feasibility, low toxicity, and simplicity of the process. In this study, extracellular synthesis of silver and zinc nanoparticle was carried out by Pseudomonas hibiscicola isolated from the effluent of an electroplating industry in Mumbai. Characterization studies revealed synthesis of 40 nm and 60 nm nanoparticles of silver (AgNP) and zinc (ZnNP) respectively with distinct morphology as observed in TEM and its crystalline nature confirmed by XRD. DLS, Zeta potential, NTA and FTIR studies further characterized nanoparticles giving data about its size, stability, and functional groups. Considering the toxicity of nanoparticles the evaluation of antimicrobial activity was studied in the range of non-toxic concentration for normal cell lines. Silver nanoparticles were found to be the most potent effective antimicrobial against all tested strains and drug resistant clinical isolates of MRSA, VRE, ESBL MDR Pseudomonas aeruginosa with MIC in the range of 1.25 – 5 mg/ml. Zinc nanoparticles were found to be specifically active against Gram positive bacteria like Staphylococcus aureus including its drug resistant variant MRSA. Both AgNP and ZnNP were found to be effectivepotent against Mycobacterium tuberculosis and its MDR strain with MIC of 1.25 mg/ml. The synergism synergistic action of nanoparticles assessed in combination with a common antibiotic Gentamicin (590 μg/mg) used for the treatment of various bacterial infections by Checker board assay. Silver nanoparticles profoundly exhibited synergistic antimicrobial activity against drug resistant strains of MRSA, ESBL, VRE and MDR Pseudomonas aeruginosa while ZnNP were found to give synergism with Gentamicin only against MRSA. The MRSA, ESBL and Pseudomonas aeruginosa strains exhibited MIC of 2.5mg/ml except VRE which was 10mg/ml for both AgNPs and ZnNPs. These results prove the great antimicrobial potential of AgNP and ZnNP against drug resistant strains of community and hospital acquired infections and opens a new arena of antimicrobials for treatment, supplementary prophylaxis, and prevention therapy.